2014
DOI: 10.1111/bju.12834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional outcomes after laparoscopic partial nephrectomy using renal scintigraphy: clamped vs clampless technique

Abstract: ObjectivesTo examine differences in postoperative renal functional outcomes when comparing clampless with conventional laparoscopic partial nephrectomy (LPN) by using renal scintigraphy, and to identify the predictors of poorer postoperative renal functional outcomes after clampless LPN. Patients and Methods Between September 2010 and September 2012, 87 patients with renal masses suitable for LPN were prospectively enrolled in the study. From September 2010 to September 2011, LPN with renal artery clamping was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 28 publications
2
34
0
1
Order By: Relevance
“…Similar findings to ours were reported by Mir et al [25] and Aertsen et al [26]. Others however, reported a direct relationship, that is, large and more complex tumors predicted postoperative AKI [27,28].…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings to ours were reported by Mir et al [25] and Aertsen et al [26]. Others however, reported a direct relationship, that is, large and more complex tumors predicted postoperative AKI [27,28].…”
Section: Discussionsupporting
confidence: 91%
“…However, after the sixth postoperative month, the global RF was not significantly influenced by the hilum management (as long as WIT was <30 min). Similarly, Porpiglia et al reported that the split RF assessed using renal scan was not significantly different in patients undergoing laparoscopic PN with off-clamp vs. modest (<25 min) ischemia [9]. Conversely, Trehan in a meta-analysis of six observational comparative studies reported a significantly longterm lower fall in eGFR in patients who underwent off-clamp PN compared to those who underwent on-clamp PN [27].…”
Section: Discussionmentioning
confidence: 97%
“…However, the use of off-clamp procedures is increasingly adopted to maximize the functional outcome after conservative surgery as prolonged ischemia time has been associated with a significantly higher RF impairment [8]. Nevertheless, a definitive functional benefit of offclamp PN has not been proved yet [3,9,10]. Beyond a possible protective effect on postoperative RF, off-clamp PN could be associated with a higher complication and positive surgical margin (SM) rate due to a higher bleeding and a subsequent suboptimal vision [11].…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence suggests that the amount of residual functional parenchyma after PN represents a significant surgical factor that impacts on post-operative renal function [9,20] and that warm ischaemia time (WIT) is a wellknown predictor of post-operative eGFR [9]. Given these findings, it would be advisable to perform a clampless partial nephrectomy removing the danger risk of sacrificing healthy parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Thompson et al [8] demonstrated that "every minute counts" when the renal hilum is clamped and that warm ischaemia time (WIT) is a well-known predictor of the post-operative estimated glomerular filtration rate (eGFR). Given this restriction, it is advisable to perform a clampless PN whenever feasible, particularly in patients with poor baseline renal function [9]. The aim of the present study was to assess the feasibility and safety of LPN for renal tumours of high surgical complexity in our single-institutional experience, comparing perioperative and functional data between clampless and clamped procedures.…”
Section: Introductionmentioning
confidence: 99%